Differences in Ethno-Linguistic Structure of Population of Subordinated to Ukraine and Occupied Territories of Donetsk and Lugansk Regions - Sklyar, Volodymyr (Київський національний університет імені Тараса Шевченка, 2018)
Based on statistical analysis the differences in ethno-linguistic structure of the population of occupied territories as separately Donetsk and Lugansk and as Donbass in general are determined. It is determined that the majority of the total population of Donbas was on the occupied territory, although the area of occupied lands as Donetsk and Luhansk was much smaller than the area free from occupation territories of these two regions. It is proved that the absolute majority of the total population of the not controlled by Ukraine territory were Ukrainians. Due to the fact that considerable part of Ukrainians was assimilated by language (Russified), Ukrainian speaking population was in the minority among the all population of the occupied territories of Donbass and free from occupation territories of Donetsk region. In spite of the Russians were a minority among the all population, on these territories by the number Russian-speaking population were dominated. Only amoung the total population of subordinated to Ukraine’s territory of Lugansk region Ukrainian speaking population was an absolute majority, and Russian-speaking population was in the minority. The level of natural language Ukrainianization of Russian ethnic minority was minimal (less than 1%). Geographical representation of ethnic minorities except for Russians on territories outside of the control of the Donbass remained very low; the majority of them were Russified by language. Ukrainian speaking Donbass population consisted almost exclusively of Ukrainian speaking Ukrainians. Among the Russian-speaking population part of Russians unlikely exceeded half, and part of Russian-speaking Ukrainian was 40 %. The longer term of the occupation of the territory of Donbass is, than the harder it will be the next process of reintegration of its population to the Ukrainian society.Keywords: Ukraine, Donbass, the Occupied and Free from Occupation Territories, the Number and Ethno-Linguistic Structure of Population, Ukrainians, Russians, Ethnic Minorities, Except the Russians, Ukrainian Speaking and Russian Speaking Population.

Володимир СклярНа основі аналізу статистичних матеріалів встановлено відмінності в етномовній структурі населення підпорядкованих Україні та окупованих територій Донбасу у цілому, а також окремо Донецької та Луганської областей. Визначено, що переважна більшість всього населення Донбасу опинилася на окупованих теренах, хоча площа окупованих земель як Донеччини, та і Луганщини була значно меншою, ніж площа вільних від окупації територій цих двох областей.  Доведено,  що  абсолютну  більшість  серед  загальної  чисельності  населення  на  підконтрольних  та непідконтрольних Україні теренах Донбасу складали українці. Внаслідок того, що значна частина українців були асимільовані за мовою (зросійщені), україномовне населення опинилося в меншості серед усього населення на окупованих територіях Донбасу, а також на вільних від окупації теренах Донеччини. Попри те, що росіяни залишалися в меншості серед усього населення, на окупованих землях Донбасу домінувало за чисельністю російськомовне населення. Лише серед усього населення на підконтрольній Україні частині Луганщини україномовне населення становило абсолютну більшість, а російськомовне населення залишалося в меншості. Рівень мовної українізації російської етнічної меншини був мінімальним (менше 1%). Територіальне представництво етнічних меншин, окрім росіян на не підконтрольних Україні територіях Донбасу було досить незначним, а переважна більшість із них виявилися зросійщеними за мовою. Україномовне населення Донбасу складалося майже винятково з україномовних українців. Серед російськомовного населення частка російськомовних росіян ледве перевищувала половину, а більше 40% складала частка російськомовних українців. Чим тривалішим буде термін окупації частини території Донбасу, тим складнішим буде процес наступної реінтеграції його населення до українського суспільства.Ключові слова: Україна, Донбас, окуповані та вільні від окупації терени, чисельність та етномовний склад населення, українці, росіяни, етнічні меншини, крім росіян, україномовне та російськомовне населення.
Відмінності в етномовній структурі населення підпорядкованих україні й окупованих територій Донецької та Луганської областей